Peran kebijakan negara dalam mengatasi ketimpangan sosial dan ekonomi di indonesia - Jannah, Khurfatul (Maliki Interdisciplinary Journal, 2025)
Social and economic inequality in Indonesia is a complex issue caused by uneven wealth distribution, rapid urbanization, and limited access to education and basic services for the community. This situation negatively impacts social stability and national progress, while also increasing the threats of social conflict and crime. The Indonesian government has implemented various programs to reduce these disparities, including wealth redistribution, infrastructure development, improving access to education and healthcare, and reforming the tax system. However, the effectiveness of these policies still faces many obstacles, such as political, economic, and cultural challenges. This research aims to explore the causes, consequences, and the role of government policies in addressing social and economic inequality in Indonesia. Through literature review and recent statistical data, this report emphasizes the need for data-driven policy development and inclusive approaches to achieve social justice. The recommendations include enhancing inter-agency coordination, strengthening community participation, and innovating social and economic policies as strategic steps toward a fairer and more prosperous society.